Let's Go Green Program: 3R (Reduce, Reuse, Recycle) co-organized by UiTM Sarawak and Majlis Perbandaran Kota Samarahan / Sharifah Nur Amirah Syed Akil - Syed Akil, Sharifah Nur Amirah (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2023)
The Let's Go Green: 3R (Reduce. Reuse. Recycle) program jointly organized by the UiTM Sarawak Curriculum Unit and Majli Perbandaran Kota Samarahan (MPKS) was organized at the Dewan Jubli of UiTM Sarawak, Samarahan Campus on 17 June 2023. This program was attended by 100 people from the community around Kota Samarahan and 300 students from UiTM Sarawak. This program also got cooperation from the Sarawak State Environment Department and the Sarawak Natural Resources and Environment Board (NREB).